2014
DOI: 10.1128/aem.01861-14
|View full text |Cite
|
Sign up to set email alerts
|

Routes of Acquisition of the Gut Microbiota of the Honey Bee Apis mellifera

Abstract: bStudies of newly emerged Apis mellifera worker bees have demonstrated that their guts are colonized by a consistent core microbiota within several days of eclosure. We conducted experiments aimed at illuminating the transmission routes and spatiotemporal colonization dynamics of this microbiota. Experimental groups of newly emerged workers were maintained in cup cages and exposed to different potential transmission sources. Colonization patterns were evaluated using quantitative real-time PCR (qPCR) to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
528
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(559 citation statements)
references
References 46 publications
(56 reference statements)
26
528
1
4
Order By: Relevance
“…In our study, all the infested bees, from both the field and cage studies, showed a significant up-regulation of transcripts from the S. alvi genome in comparison with the uninfested ones (see data from Experiments 2 and 3 below). Previous studies investigating the composition of bee's core microbiota found that A. mellifera workers eclose without core resident bacteria and with a few bacteria of every kind (Gilliam, 1971;Martinson et al, 2012) and develop a stable microbial community by day 4e6 after exposure to the natural hive conditions (Powell et al, 2014;Anderson et al, 2015). This was certainly possible for bees from the field study but more difficult for those from the cage studies, since they were collected at the L5 stage and transferred to the lab until eclosion and sampled immediately after, in the case of newly emerged bees, or maintained in cages until sampling, in the case of adult bees.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, all the infested bees, from both the field and cage studies, showed a significant up-regulation of transcripts from the S. alvi genome in comparison with the uninfested ones (see data from Experiments 2 and 3 below). Previous studies investigating the composition of bee's core microbiota found that A. mellifera workers eclose without core resident bacteria and with a few bacteria of every kind (Gilliam, 1971;Martinson et al, 2012) and develop a stable microbial community by day 4e6 after exposure to the natural hive conditions (Powell et al, 2014;Anderson et al, 2015). This was certainly possible for bees from the field study but more difficult for those from the cage studies, since they were collected at the L5 stage and transferred to the lab until eclosion and sampled immediately after, in the case of newly emerged bees, or maintained in cages until sampling, in the case of adult bees.…”
Section: Resultsmentioning
confidence: 99%
“…Microbiome inheritance: perpetuation of a microbiome between hosts, typically between parent and offspring, but also between mates [80], siblings or other relatives (e.g., between members of a social-insect colony [61]…”
Section: Methods 2: Selection Upon Hosts In Diverging Microbiomesmentioning
confidence: 99%
“…Vertical transmission can occur via a diversity of pathways, including transovarial transmission, or via behavioral mechanisms such as a mother coating an egg casing with bacteria which the offspring then acquires upon hatching [49,54]. Likewise, components of the human microbiome are inherited from a mother during or even before birth [53,60], and the honeybee gut microbiome of eight bacterial species[ 1 _ T D $ D I F F ] clusters is inherited by newborn bees from sibling workers or the hive environment [61,62]. Importantly, vertical transmission of microbiomes can occur with different degrees of fidelity, measured as the likelihood with which an individual microbial genotype or whole community is passed successfully from mother to offspring.…”
Section: How Does Host-mediated Selection Alter the Makeup Of The Micmentioning
confidence: 99%
“…A central feature of many social and subsocial insects is the intimate interaction of conspecifics through behaviours such as trophallaxis, the transfer of food or other fluids through mouth-to-mouth (stomodeal) or anus-to-mouth ( proctodeal) feeding [27]. These behaviours can facilitate exchange of microbes among nest members, thereby contributing to maintenance of a beneficial microbiota, as has been demonstrated in ants [16,28,29], termites [30] and bees [31,32]. In fact, it has been speculated that the evolution of complex social forms could be reinforced, among other factors, by the convenience of acquiring beneficial microbes through recurring contact with conspecifics [33].…”
Section: (C) Social Acquisitionmentioning
confidence: 99%
“…In honeybees (Apis mellifera), workers lack this distinctive microbial community upon eclosion, and recent findings demonstrate that they acquire the most dominant members of the microbiota either through social contact with nestmates (trophallaxis), specifically nurses, or via contact with the hive components (e.g. combs and honey) [32,36]. As for bumblebees, molecular analyses carried out across three host species (B. sonorus, B. impatientis and Bombus sp.)…”
Section: (C) Social Acquisitionmentioning
confidence: 99%